IKLAN LAYANAN MASYARAKAT ETIKA BERKOMUNIKASI MASYARAKAT MINANG DI SITUS JEJARING SOSIAL - ade moussadecq; Agung Eko BW; Rosta Minawati (Jurusan Seni Rupa, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2018)
Surveys from APJII conducted in 2016, states 1.8 million or 35% of people in the province of West Sumatra have been connected to the Internet and often access social networking sites like Facebook and Twitter. The low ethics of social media of some people causes them to write down the status of SARA. In the Minangkabau community, known ethics communicate organize communications that are compatible with the morma and cultural values ​​of Minangkabau, namely